Perencanaan Volume Injeksi CO2 Dan Tekanan Injeksi CO2 Dengan Pola Injeksi ¼ Dari 5 Spot Pada Kegiatan CO2 Flooding-Enhanced Oil Recovery (CO2EOR) Di Sumur "TRK-15" Lapangan "KLMT" - Refiyanto, Andra Agustin; Risna, Risna; Afifah, Rohima Sera (JST (Jurnal Sains Terapan), 2023)
The "TRK-15" well in the “KLMT” field is classified as an old well located in Jambi Province. This study focuses on calculating CO2 injection volume and CO2 injection pressure using 4 injection rate parameters by applying the CO2 flooding design method. The research method used is the CO2 flooding-enhanced oil recovery method. CO2 flooding design calculations focus on the amount of CO2 injected and CO2 injection pressure with 4 injection rate parameters (qi) starting from 5 Mscfd, 10 Mscfd, 15 Mscfd, 20 Mscfd. Based on the research results based on 4 injection rate parameters (qi), for an injection rate (qi) of 5 Mscfd, the CO2 front time (tCO2) = 50.03 hours and the amount of CO2 needed for injection (VCO2) = 3,481,790.4 scf. For the injection rate parameter (qi) of 10 Mscfd, the CO2 front time (tCO2) = 25.01 hours and the amount of CO2 required for injection (VCO2) = 1,742,136.48 scf. For the injection rate parameter (qi) 15 Mscfd, the CO2 front time (tCO2) = 16.67 hours and the amount of CO2 required for injection (VCO2) = 1,162,458.72 scf. For the injection rate parameter (qi) 20 Mscfd, the CO2 front time (tCO2) = 12.51 hours and the amount of CO2 required for injection (VCO2) = 871,999.2 scf. For the injection rate parameter (qi) 5 Mscfd, CO2 tubing injection pressure (Ptf) = 227.95 psi, for the injection rate parameter (qi) 10 Mscfd obtained (Ptf) = 903.43 psi, for the injection rate parameter (qi) 15 Mscfd obtained (Ptf) = 2,025.51 psi, for the injection rate parameter (qi) 20 Mscfd obtained (Ptf) = 3,594.03 psi. Keywords : CO2 Flooding, Enhanced Oil Recovery, Production Flow Rate